Pengembangan tool pemodelan eksperimen gerak melingkar beraturan dengan pengontrolan laju motor DC berbantukan analisis video tracker (Development of experimental modeling tools for regular circular motion with DC motor speed control assisted by video tracker analysis) - Cici Putri; - Asrizal (Department of Physics – Universitas Negeri Padang UNP, 2019)
The development of technology and information can provide influence on the progress of Science and Technology. Improved science is supported by the role of media and digital technology. Physics is one of the sciences relating to experimental activities. One of interesting is the phenomenon of uniform circular motion. Based on observations were known that the experimental activities use manual tool that have limitations in displaying measurement data. This problem can be solved by modeling tool with video tracker analysis. The purposes of the research were to determine the performance specifications of the uniform circular motion experiment modeling tool, determine the accuracy and precition of controlling the DC motor speed, determine the accuracy and precition of the uniform circular motion modeling tool, determine the parameters of physics and their influences on the experiment of uniform circular motion. This research method was called research and development which is a research method used to validate and develop products. Based the research can describe four results. The first, performance specification consisted of a uniform circular motion modeling tool of 20x20x10 cm by controlling the speed of a DC motor. Second, the accuracy and precition of controlling the DC motor speed with values of 98.85% and 98.54%. Third, the accuracy and precition of the uniform circular motion modeling tool with an accuracy value of 98.67% and precition value of 97.70%. Fourth, the frequency and angular velocity will be greater by using a higher speed value. However, the period value decreases as the speed increases. The influence of physics parameters is done by using variations in speed and radius. Speed is inversely proportional to period. However, speed is directly proportional to frequency and angular velocity. The effect of the radius variation is the centripetal acceleration is directly proportional to the radius